Yoga for Sleep Quality in Menopausal Women: A Scoping Review - Wilwadana, I Putu Dimasatya; Giri, Made Kurnia Widiastuti; Rahmayani, Irma (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Introduction: Sleep disturbance is one of the most frequent complaints among menopausal women, strongly associated with hormonal decline and vasomotor symptoms. While pharmacological treatments such as hormone therapy and benzodiazepines are effective, they also carry significant risks, including cardiovascular events, cancer, and cognitive decline. This has led to growing interest in safe, non-pharmacological interventions such as yoga. Method: This scoping review was conducted in accordance with the PRISMA-ScR guidelines. Literature searches were conducted in PubMed, ScienceDirect, and Google Scholar, encompassing publications from 2015 to 2025. Eligible studies included original research that investigated yoga interventions targeting sleep quality among menopausal or postmenopausal women. Randomized controlled trials (RCTs), quasi-experimental studies, and observational studies were considered if validated measures of sleep quality were reported. Discussion: Yoga interventions, commonly practiced 2–3 sessions per week for 8–12 weeks, consistently demonstrated improvements in subjective sleep quality, sleep latency, and overall well-being. Some studies also reported reductions in anxiety, depression, and vasomotor symptoms. The underlying mechanisms are likely multifactorial, including regulation of the autonomic nervous system, reduction of sympathetic activity, promotion of parasympathetic balance, and hormonal modulation. When compared with other non-pharmacological interventions such as Tai Chi and Qigong, yoga showed comparable benefits. Hormone therapy remains the most effective for vasomotor-related insomnia, yet yoga offers a safer long-term alternative with no reported serious adverse effects. Conclusion: Yoga is a safe, feasible, and effective non-pharmacological intervention to improve sleep quality in menopausal women and may serve as a complementary option alongside conventional treatments.